An evaluation of recruitment and selection processes in three organizations in the UAE - Al Tunaiji, Hessa Abdulla (2011)
Recruitment and selection activities play an important role in all organizations. The use of formal and informal recruitment and selection procedures for Human Resource Management has increased dramatically in United Arab Emirates (UAE) organizations. The main objective of this research is to investigate the current effectiveness of recruitment and selection in three UAE organizations assessing strengths and weaknesses as well as comparing them with models of best practice. This dissertation reviews current literature on recruitment and selection processes, discusses the best practice models of recruitment and selection, and engages in case study research and interviews with HR directors and supervisors in organizations in the UAE. The major findings indicate that, over last few years, UAE organizations faced some difficulty in understanding how defined recruitment and selection procedures should be. They have tended to confuse various processes or miss out some of the critical steps. Nevertheless, organizations recruited considerably, and particularly during the boom years, however since it is not a professional way of resourcing, companies faced other problems such as high recruitment costs and employee turnover. This case study research reveals strong variation in recruitment and selection policies and practices in the small sample of three UAE organizations and also shows some significant areas of divergence from best practice models. Finally, some recommendations are offered to assist UAE organizations with focusing more carefully on good practice, changing and developing solutions to minimize the problems that typically arise from inadequate recruitment and selection processes.